Eine empirische Analyse der Nutzungsintensität von Smartphones in der deutschen Landwirtschaft; An Empirical Study of Smartphone Use Intensity in German Agriculture - Marius Michels; Oliver Mußhoff (German Journal of Agricultural Economics (GJAE), 2020)
– Smartphone apps and the inbuilt-sensors can be seen as a subarea of precision farming technologies. Furthermore, an increase in smartphone-based decision support tools is observed in the last years. While the adoption of smartphones and willingness to pay for apps by farmers were already investigated, little is known about the use intensity of smartphones in agriculture. Against this background, 272 German farmers were asked how many agriculture-themed apps they are using. A negative binomial regression is applied to analyze the determinants of the smartphone use intensity measured in the number of used apps. Besides other factors, our results show that the use intensity is statistically significantly affected by farmers' age and education. No statistically significant effect is found for satisfaction with mobile internet coverage. Our results are of interest for developers and providers of apps as well as policy makers as they provide first essential information about the use intensity of smartphone-based decision support tools in agriculture. Aspects of data security should be recognized in the development of public training programs in terms of digitalization. Moreover, the interface of an app and the presentation of information through the app should be kept simple to be useful for all farmers.
Keywords: 330